After the crisis, back to basics - Mahamane, Brah (Technical Centre for Agricultural and Rural Cooperation, 1987)
In response to the 'Viewpoint' article by Jacques Hecq published in the previous issue of SPORE, was this reaction from Brah Mahamane, Executive Secretary of CILLS. The first consequence of the long drought that we experienced in the Sahel from...